2019
DOI: 10.1136/oemed-2018-105545
|View full text |Cite
|
Sign up to set email alerts
|

Functional variant of the carboxypeptidase M (CPM) gene may affect silica-related pneumoconiosis susceptibility by its expression: a multistage case–control study

Abstract: ObjectivesIn a genome-wide association study, we discovered chromosome 12q15 (defined as rs73329476) as a silica-related pneumoconiosis susceptibility region. However, the causal variants in this region have not yet been reported.MethodsWe systematically screened eight potentially functional single-neucleotide polymorphism (SNPs) in the genes near rs73329476 (carboxypeptidase M (CPM) and cleavage and polyadenylation specific factor 6 (CPSF6)) in a case–control study including 177 cases with silicosis and 204 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The characteristics of the 177 SPF cases and 204 healthy workers recruited from Wuxi who were exposed to silica dust are entirely consistent with those of our previously published studies . Additional 126 SPF cases were recruited in 2017 from Datun Mining Business Group Co. Ltd. of Xuzhou in Jiangsu Province, with 126 healthy worker controls randomly selected from a pool of >1000 individuals with occupational dust exposure who participated in the routine health surveillance in 2017 in Xuzhou.…”
Section: Methodssupporting
confidence: 64%
“…The characteristics of the 177 SPF cases and 204 healthy workers recruited from Wuxi who were exposed to silica dust are entirely consistent with those of our previously published studies . Additional 126 SPF cases were recruited in 2017 from Datun Mining Business Group Co. Ltd. of Xuzhou in Jiangsu Province, with 126 healthy worker controls randomly selected from a pool of >1000 individuals with occupational dust exposure who participated in the routine health surveillance in 2017 in Xuzhou.…”
Section: Methodssupporting
confidence: 64%
“…In addition, silicosis, which is a chronic progressive fibrotic lung inflammation, may increase the risk of COPD. Research indicates that the functional variant of the CPM gene 16 and the rs2609255 polymorphism in the FAM13A gene 17 are associated with silicosis susceptibility in a Chinese population. In our study, we discussed the susceptibility of SREK1 rs74794265 C>T polymorphism in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Genomics studies on silicosis suggest that single nucleotide polymorphisms are associated with susceptibility to pneumoconiosis and several disease-related single nucleotide polymorphisms have been found ( eg , rs73329476, rs12812500). [ 60 ] Epigenomics studies have shown that some miRNAs are closely associated with pneumoconiosis risk and disease progression, and have the potential to serve as non-invasive biomarkers and prognostic markers for early pneumoconiosis. [ 61 , 62 ] Transcriptomics and proteomics identify a range of differentially expressed protein-coding genes and proteins.…”
Section: Future Research Prospectsmentioning
confidence: 99%